A study on fractional HIV‐AIDs transmission model with awareness effect. (7th October 2021) - Kumar, Sunil; Chauhan, Ram P.; Osman, Mohamed S.; Mohiuddine, S. A.
Abstract : The main aim of this work is to numerically investigate a mathematical model of the HIV/AIDS disease with awareness effect, as the fractional derivatives capture more the genetic and memory properties of the biological models in comparison to the classical derivative. Therefore, in this article, we utilize the generalized Caputo fractional derivative to extend the integer‐order model of HIV/AIDS transmission to fractional order. A novel fixed‐point approach is used to identify the existence and uniqueness of the FO model. We use a new numerical technique based on the Adams‐Bashforth predictor‐corrector method to solve the fractional‐order HIV/AIDS transmission model. We illustrated the obtained numerical results through graphs.